Is serum homocysteine level a biomarker of suicide attempts: A preliminary study - Susam, Solmaz; Ilhan, Nevin; Bodur, Akin; Cikim, Gurkan; Canpolat, Omer (Pergamon-Elsevier Science Ltd, 2024)
Suicide is a global public health concern, and understanding its multifaceted determinants is crucial for effective prevention. This study was designed to find an answer to the question of whether serum homocysteine level can be a biomarker of suicide attempts. This preliminary study involving 90 participants (45 suicide attempt cases and 45 controls) was conducted at Elazig Fethi Sekin City Hospital. Biochemical analyses were performed to assess serum homocysteine, vitamin B12, and folic acid levels. Statistical analyses, including t-tests, Mann-Whitney U tests, and ROC analysis, were employed to explore differences between groups and assess the diagnostic potential of homocysteine. Elevated homocysteine levels were found in individuals who attempted suicide compared to the control group (p= <0.001). Additionally, lower levels of vitamin B12 (p=<0.001) and folic acid (p=<0.001) were observed in the suicide attempt group. ROC analysis indicated a significant diagnostic potential for homocysteine in predicting suicide attempts (AUC = 0.845, sensitivity = 91%, specificity = 71%). This study establishes a significant association between high homocysteine levels and suicide attempts, accompanied by lower vitamin B12 and folic acid levels. The findings suggest a potential link between disturbances in homocysteine metabolism and suicidal tendencies, urging further research to establish causation and explore therapeutic implications. Consideration of the study's limitations and directions for future research are warranted.
Keywords: Vitamin B12; Folic acid; Homocysteine; Suicide attempts